Comprehensive Analysis and Development of Comfortable Energy Saving Measures of Buildings - Abdinazarovich, Asatov Nurmuhammad; Kosimovich, Kosimov Turaboy; Khatam Ugli, Aralov Tokhir; Abror Ugli, Mukhtarov Marufkhzha (European Journal of Life Safety and Stability (2660-9630), 2022)
The question of the comfort of residential, public and industrial buildings, taking into account energy efficiency, has been and remains one of the priority areas for the health and safety of mankind. The article provides a comprehensive analysis and programs of energy-saving measures to improve the energy efficiency of buildings. Performed thermo technical calculation of existing enclosing structures.